The Influence of Generative AI on Content Creation and Consumer Trust in Global Markets - Andri Catur Trissetianto; Ridwan (Greenation Publisher, 2025)
The rapid integration of generative AI in digital marketing has transformed content creation and consumer engagement globally. This study investigates the influence of generative AI on content creation and consumer trust in global markets. The research employs a mixed-methods approach, combining quantitative analysis of global marketing campaigns with qualitative insights from consumer surveys and expert interviews. The findings reveal that generative AI enhances content personalization and operational efficiency, leading to increased consumer engagement. However, consumer trust is contingent upon transparency, ethical use, and regional considerations. The study underscores the importance of ethical frameworks and strategic localization to maximize AI's benefits while mitigating associated risks. This research provides valuable insights into the evolving role of AI in global digital marketing, offering a foundation for future studies on AI's impact on consumer behavior and marketing strategies.